1994
DOI: 10.1177/095646249400500511
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Early Colposcopy in the Management of Females with First Episode Anogenital Warts

Abstract: 212 females attending a genitourinary medicine (GUM) clinic with first episode anogenital warts were screened by cervical cytology and colposcopy/histology for the presence of cervical epithelial abnormalities in keeping with infection by the human papillomavirus (HPV infection) and/or cervical intraepithelial neoplasia (CIN). The prevalence of cervical epithelial abnormalities detected by cervical cytology alone was 32%, rising to 56% after colposcopic examination. However, the majority of cervical lesions de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…'3 Colposcopy studies of women with vulval warts, performed before widespread cytology screening began, showed high levels (16-9%) of CIN 2 and 3,14 but more recent studies have shown much lower levels of 0_3.3%. [15][16][17] In the one study with a control group there was no difference in the colposcopy findings of the women with warts and the controls. 15 The NHS Cervical Screening Programme guidelines'8 recommended that women presenting with vulval warts should have a cervical smear taken and the result should determine whether or not colposcopy is needed.…”
mentioning
confidence: 87%
“…'3 Colposcopy studies of women with vulval warts, performed before widespread cytology screening began, showed high levels (16-9%) of CIN 2 and 3,14 but more recent studies have shown much lower levels of 0_3.3%. [15][16][17] In the one study with a control group there was no difference in the colposcopy findings of the women with warts and the controls. 15 The NHS Cervical Screening Programme guidelines'8 recommended that women presenting with vulval warts should have a cervical smear taken and the result should determine whether or not colposcopy is needed.…”
mentioning
confidence: 87%